2015
DOI: 10.1186/s12870-015-0556-8
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic shoot meristem generation in monocotyledonous rpk1 mutants is linked to SAM loss and altered seedling morphology

Abstract: BackgroundIn dicot Arabidopsis thaliana embryos two cotyledons develop largely autonomously from the shoot apical meristem (SAM). Recessive mutations in the Arabidopsis receptor-like kinase RPK1 lead to monocotyledonous seedlings, with low (10 %) penetrance due to complex functional redundancy. In strong rpk1 alleles, about 10 % of these (i. e. 1 % of all homozygotes) did not develop a SAM. We wondered whether RPK1 might also control SAM gene expression and SAM generation in addition to its known stochastic im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…At the heart stage, both the embryo and suspensor of the rpk1 toad2 mutant undergo abnormal morphogenesis, resulting in impaired embryos typically arrested at the late globular stage with a characteristic toadstool shape ( Nodine et al., 2007 ). Moreover, RPK1 and TOAD2 are required to specify cell types of the apical embryonic domain that produces cotyledon primordia ( Nodine and Tax, 2008 ; Fiesselmann et al., 2015 ). Some rpk1 seedlings miss one cotyledon due to disturbed PIN1 polarity and auxin homeostasis in defective embryos at early developmental stages ( Luichtl et al., 2013 ).…”
Section: Rlks Regulate Embryo Developmentmentioning
confidence: 99%
“…At the heart stage, both the embryo and suspensor of the rpk1 toad2 mutant undergo abnormal morphogenesis, resulting in impaired embryos typically arrested at the late globular stage with a characteristic toadstool shape ( Nodine et al., 2007 ). Moreover, RPK1 and TOAD2 are required to specify cell types of the apical embryonic domain that produces cotyledon primordia ( Nodine and Tax, 2008 ; Fiesselmann et al., 2015 ). Some rpk1 seedlings miss one cotyledon due to disturbed PIN1 polarity and auxin homeostasis in defective embryos at early developmental stages ( Luichtl et al., 2013 ).…”
Section: Rlks Regulate Embryo Developmentmentioning
confidence: 99%
“…Notably, the RPK1 homolog RPK2 regulates WUS expression to control SAM maintenance, and, although this function is not conserved in RPK1 [ 89 ], the two proteins show redundancy during embryogenesis and their sequences mainly differ in the kinase domain [ 81 , 86 ], indicating that they might simply respond to different external cues. Nonetheless, SAM-less monocotyledonous rpk1 mutants are capable of expressing shoot markers and occasionally regenerate ectopic shoot meristems [ 90 ]. Motte et al further showed that early and late regeneration characteristics are poorly correlated, indicating that the shoot organogenetic process can be inhibited at several intermediate stages and chlorophyll maturation does not ensure successful shoot determination [ 11 , 81 ].…”
Section: Mapping Natural Variation In the Organogenic Potential Atmentioning
confidence: 99%